Gilles Deleuze's luminous philosophy - Berressem, Hanjo, 1956- (Edinburgh University Press, 2020)
Engaging the whole body of Deleuze's work, including less rehearsed texts such as The Actual and the Virtual, Lucretius and the Simulacrum and his lectures on Spinoza, Hanjo Berressem traces the 'line of light' that runs through Deleuze's thought.